Gambaran Subjective Well-Being Guru TK Di Kecamatan Limbangan - Wardani, Elia; Sabrina, Nazah Wardah (LP2M STAI Al-Musaddadiyah Garut, 2025)
This study aims to provide an overview of the subjective well-being levels of kindergarten teachers in Limbangan District and to identify the most dominant component and the most influential factor affecting their well-being. This research employs a descriptive qualitative method with purposive sampling, involving 60 kindergarten teachers in Limbangan District. Data were collected using a Likert-scale questionnaire measuring three main components of subjective well-being: life satisfaction, positive affect, and negative affect, followed by the calculation of subjective well-being scores. The subjects of this study were kindergarten teachers teaching at schools within Limbangan District, totaling 60 participants. The results indicate that the majority of kindergarten teachers in Limbangan District have high to very high levels of subjective well-being (80% of total participants). The most dominant component is life satisfaction, while the most influential factor is income. Keywords: subjective well-being; kindergarten teacher; cognitive